Developing A Mobile Web for Innovative University Assessment System: Thailand Talent Mobility Programme - Kongsoontornkijkul, Kritika; Pichyangkura, Rath; Vadhanasindhu, Pakpachong; Vanichbuncha, Kanlaya (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Empirical research methods were used to study the Thailand Talent Mobility Programme and critical factors effecting participation in the project; from the perspectives of academic researchers in Science, Technology, and Innovation, in order to strengthen the competitiveness of technological innovation in Thailand. On the basis of questionnaire surveys of 58 universities and 17 research institutes, 613 academic researchers across the country responded the survey. All responses were analyzed through factor analysis and regression analysis methods. We conducted a thorough study of the impact of all factors to successful programme participation. This research study also identifies recommendations and solutions for successful personnel sharing models in Thailand. A mobile web for innovative university assessment system is also introduced as a supporting tool.